Analisis Kontrol Masyarakat terhadap Penegak Hukum pada Trend No Viral No Justice dalam Mewujudkan Keadilan - Sihaloho, Hasiholan; Sudarto, Sudarto (Neolectura, 2025)
The rapid advancement of digital technology has transformed social dynamics, particularly in law enforcement oversight in Indonesia. The phenomenon of